Peran Guru dalam Menumbuhkan Apresiasi Sastra Siswa Kelas VI SDN 2 Mata IE - Aceh Besar Tahun Pelajajaran 2024/2025 - Hutabarat, Imelda; Suharti, Sri (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2025)
This research aims to determine the learning strategies used by teachers at SDN 2 Mata Ie-Aceh Besar in fostering student appreciation for literary works, using qualitative research methods, so that data is collected through observation, interviews comparing student work results from 3 meetings. The research results show that in learning activities teachers use strategies learning, namely: 1) reading local literary folk tales loudly and clearly in front of the class entitled